Impact of the COVID-19 pandemic on athletes belonging to the Japan Professional Football League - Sasaba, I.; Murakami, K.; Hayashi, Y.; Sakuma, H. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
Introduction The coronavirus disease of 2019 (COVID-19) pandemic has led to dramatic changes in the sports environment (Grix, Brannagan, Grimes, & Neville, 2021). The changes in the sports environment have impacted psychologically on athletes.